Conservation Priority Plants in Bukit Barisan Selatan National Park - Syamsul Hidayat; Esti Munawaroh (Media Konservasi, 2019)
Bukit Barisan Selatan National Park (BBSNP) has a fairly high biodiversity, including plant species which are categorized as threatened, protected and endemic plants in Sumatra. Information regarding the existence of these plant species is not yet widely available. The purpose of this study was to reveal the existence of threatened, protected and endemic plant species in BBSNP. The research was conducted by exploration methods in three BBSNP areas, namely Kubu Prahu (West Lampung Regency), Sukaraja Atas (Tanggamus Regency) and Rata Agung (Pesisir Barat Regency). A number of target species have been obtained, including 13 threatened plant species, 6 protected plant species, and 7 endemic Sumatran plant species. In addition, three plant species have been included in CITES Appendix 2. The results of the study can be used as a reference for future flora conservation efforts. Keywords: BBSNP, endemic plant, protected, threatened